Homemade modern : smart DIY designs for a stylish home - Uyeda, Ben (Running Press, 2015)
30 Attractive Projects You'll Actually Want to Make. Everyone is capable of making useful things, and beautifully made modern furniture shouldn't cost thousands of dollars. In HomeMade Modern you'll learn to make the furniture you want at a fraction of the price of store-bought furniture. Not only will you save tons of money, but you'll also make environmentally sustainable pieces that are solidly built, using real materials like metal, wood, concrete, and other recycled ready-mades. The projects in this book don't require special skills, prior experience, or even a garage full of tools. This book will walk you step-by-step through the process of making furniture, from where to buy the materials (or where to scavenge!) to how to make the most of the tools you own. All you need is a sense of adventure to make furniture that looks amazing and that you can actually afford.